2023
DOI: 10.1002/lio2.1032
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic utility of diffusion‐weighted magnetic resonance imaging and high‐resolution computed tomography for cholesteatoma: A meta‐analysis

Abstract: Objective: The purpose of this meta-analysis was to compare the efficiency of highresolution computed tomography (HRCT) and diffusion-weighted magnetic resonance imaging (DWI) in guiding the diagnosis of middle ear cholesteatoma in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
3
3
Order By: Relevance
“…This percentage is considerably better than previous studies such as Nash et al [9], who reported a sensitivity of 63.6%. However, our reported sensitivity was lower than other studies [88%, 89.3%, and 100.0%] [10][11][12] . The studies by Xun et al [10] and Laske et al [11] included a large sample of patients, and the study by Osman et al [12] included only subjects with recurrent conditions.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…This percentage is considerably better than previous studies such as Nash et al [9], who reported a sensitivity of 63.6%. However, our reported sensitivity was lower than other studies [88%, 89.3%, and 100.0%] [10][11][12] . The studies by Xun et al [10] and Laske et al [11] included a large sample of patients, and the study by Osman et al [12] included only subjects with recurrent conditions.…”
Section: Discussioncontrasting
confidence: 95%
“…However, our reported sensitivity was lower than other studies [88%, 89.3%, and 100.0%] [10][11][12] . The studies by Xun et al [10] and Laske et al [11] included a large sample of patients, and the study by Osman et al [12] included only subjects with recurrent conditions. This could explain the heterogeneity of sensitivities.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…While our study centered on HRCT, it's important to acknowledge the complementary role of MRI in cases where intricate soft tissue characterization is essential. Incorporating advanced imaging modalities like diffusion-weighted (DW) MRI, as recommended by recent studies [ 12 ], could further enhance our understanding of cholesteatoma and its differentiation from other middle ear pathologies. However, given the limitations of our study, exploring these innovative approaches would require separate investigations in the future.…”
Section: Discussionmentioning
confidence: 99%